Geoenvironmental practices and sustainability : linkages and directions - Sivakumar Babu, G. L.; Reddy, Krishna R.; De, Anirban; Datta, Manoj (Springer, 2017)
This volume is a compilation on issues related to sustainable practices in geo-environmental engineering, particularly as applying to developing nations such as India. While, the developed world has already developed some solutions such as landfills, developments in landfills, barriers and liners in the North America and waste-to-energy and waste incineration in Europe, developing countries like India are trying to figure out ways which suit the present condition without compromising the future needs and comforts. This volume presents case studies on the various problems and solutions adopted for different sites. Although a common approach for all the problems is not feasible or recommend, this collection aims to provide a compendium on the current efforts underway and to help achieve common ground for the practitioners and researchers involved. The works included here give insight to the possible development of resilient and sustainable structures (like offshore wind turbines) and energy geotechnics. The book covers topics such as liners and barrier systems, use of recycled and waste materials, waste management and hazard assessment, sustainable infrastructure, and sustainability and the environment. The contents of this book will be useful to researchers and professionals working in geo-environmental engineering. The book will also be useful to policy makers interested in understanding geotechnical concerns related to sustainable development.
Includes indexes.
Keywords: Environmental geotechnology.; elektronické knihy; electronic books